High Intensity Focused Ultrasound versus Brachytherapy for the Treatment of Localized Prostate Cancer: A Matched-Pair Analysis. (19th August 2015) - Aoun, Fouad; Limani, Ksenija; Peltier, Alexandre; Marcelis, Quentin; Zanaty, Marc; Chamoun, Alexandre; Vanden Bossche, Marc; Roumeguère, Thierry; van Velthoven, Roland
Abstract : Purpose . To evaluate postoperative morbidity and long term oncologic and functional outcomes of high intensity focused ultrasound (HIFU) compared to brachytherapy for the treatment of localized prostate cancer. Material and Methods . Patients treated by brachytherapy were matched 1 : 1 with patients who underwent HIFU. Differences in postoperative complications across the two groups were assessed using Wilcoxon's rank-sum or χ 2 test. Kaplan-Meier curves, log-rank tests, and Cox regression models were constructed to assess differences in survival rates between the two groups. Results . Brachytherapy was significantly associated with lower voiding LUTS and less frequent acute urinary retention (p < 0.05 ). Median oncologic follow-up was 83 months (13–123 months) in the HIFU cohort and 44 months (13–89 months) in the brachytherapy cohort. Median time to achieve PSA nadir was statistically shorter in the HIFU. Biochemical recurrence-free survival rate was significantly higher in the brachytherapy cohort compared to HIFU cohort (68.5% versus 53%, p < 0.05 ). No statistically significant difference in metastasis-free, cancer specific, and overall survivals was observed between the two groups. Conclusion . HIFU and brachytherapy are safe with no significant difference in cancer specific survival on long term oncologic follow-up. Nonetheless, a randomized controlled trial is needed to confirm these results.